Legitimazing of Collaborative Learning as a recommended learning model in society 5.0 era in Indonesia - Pohan, Albert Efendi; Noviarti, Noviarti; Saipul, Mukmin (CAHAYA PENDIDIKAN, 2023)
A suitable learning model greatly reassurances the learning effective, learning outcomes and students’ competencies in dealing uncertainty changes in society 5.0 era. This study drives to legitimize strongly that the collaborative learning model is a suitably model which urgently to be set-off to advance students' competence in fronting the society 5.0 era in Indonesia. To achieve the research ambitions, a qualitative method which systematic literature review design was orchestrated. Research data was poised by collecting 20 previous research judgement from the internet approximately the results of collaborative learning model implementation. Data analysis performance consist of data collection, data presentation, data condensation, and drawing conclusions. The analysis fallouts: 1) Collaborative learning is a learning model which has been empirically proven to be appropriate for Indonesian English teachers to apply in society 5.0 era. 2) The application of collaborative learning model has been empirically proven to increase the students’ competencies needed in society 5.0 era, namely English communication skills, critical thinking, collaboration skills, and solving problems skills. Subsequently, this research seeks out that collaborative learning model is a recommended model to be applied by Indonesian English teachers to produce the excellence graduates to fronting the vagueness in society 5.0 era in Indonesia